A new structure and theoretical analysis on leakage and performance of an oil-free R290 rolling piston compressor. (January 2015) - Wu, JianHua; Chen, Ang
Abstract: Lubricating oil improves the reliability of compressors and systems, whereas increases the system complexity. Compared with other types of compressors that have oil-free models, a rolling piston compressor has more leakage paths and bigger leakage loss. Therefore, the leakage is an important problem to be solved in order to develop an oil-free rolling piston compressor. The paper put forward a new structure of rotary compressor adopting a low pressure shell, connecting the cavities within piston and behind vane to the cavity at suction pressure and using radial compliance mechanisms. Then the leakage models were developed to calculate the mass flow rates within both the present rolling piston compressor without any oil as sealant and the new structure of oil free compressor. Results showed that by the new structure, the influences of leakage on the performance of a R290 oil free rolling piston compressor can be largely decreased. Highlights: The potentials and difficulties of oil-free R290 rotary compressor are discussed. A new structure of the oil-free compressor is proposed to reduce its leakage loss. Calculating models are discussed to calculate precisely the leakage flow rate. The leakage loss can be decreased to an acceptable value by the new structure.